Sulfonated Sargassum horneri carbon as solid acid catalyst to produce biodiesel via esterification. (March 2021) - Cao, Minghe; Peng, Libo; Xie, Qinglong; Xing, Kainan; Lu, Meizhen; Ji, Jianbing
Highlights: Sargassum horneri is utilized as catalyst for esterification reactions. The successful grafting of –SO3 H groups is confirmed by FT-IR and XPS. The oleic acid conversion of >96% was obtained at optimal conditions. The catalyst shows remarkable regenerability. Abstract: A solid acid catalyst prepared by sulfonated Sargassum horneri carbon was utilized for the esterification reaction of oleic acid and methanol. The formed amorphous carbon layers during carbonization and the access of sulfonic acid groups during sulfonation can catalyze the esterification reaction for biodiesel preparation efficiently. The catalyst was characterized by various methods to investigate its physical and chemical properties. With carbonization at 300 °C for 2 h followed by sulfonation at 90 °C for 5 h, the catalyst reached acid density of 1.40 mmol/g. The catalyst dosage, methanol/oleic acid (molar ratio), reaction temperature, and reaction time were optimized to 10 wt%, 15:1, 70 °C, and 3 h, respectively. Under the optimal condition, the conversion of oleic acid reached 96.4%. Additionally, the catalyst was regenerated after four cycles, with the conversion of oleic acid still reaching 95.4%.